An examination of knowledge acquisition (KA) requirements and practices within the gas turbine energy industry - does effective KA impact reliability and availability? - Ingham, James (Cranfield University, 2009)
In order to manage a modern day gas turbine plant, an operator must collect and disseminate a wide range of knowledge, for decision making and for reporting to high level management. Often, an operator must also justify its decisions to a parent company. A key element of power plant management is the use of maintenance strategy, in order to maintain its equipment in an adequate condition so as to reliably produce power when required. This thesis seeks to explore and define the links between effective knowledge management and effective power plant management, which are explored to produce a replicable best practice methodology for a human capital and technology driven KM system in order to enhance operator profitability.
Keywords: gas turbine; power plant management; maintenance strategy; effective knowledge management; KM system